2017
DOI: 10.1371/journal.pone.0190187
|View full text |Cite|
|
Sign up to set email alerts
|

Accounting for tourism benefits in marine reserve design

Abstract: Marine reserve design often considers potential benefits to conservation and/or fisheries but typically ignores potential revenues generated through tourism. Since tourism can be the main source of economic benefits for many marine reserves worldwide, ignoring tourism objectives in the design process might lead to sub-optimal outcomes. To incorporate tourism benefits into marine reserve design, we develop a bioeconomic model that tracks tourism and fisheries revenues through time for different management optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…Another conclusion (which probably does not need to be explained) is that optimal reserves are prominent when intrinsic habitat value is high. This result is consistent with the findings of Viana et al (2017), who found the size of reserves should be larger with increasing tourism value, which was tied to increased stock density. In their analysis, however, tourism and fishing were essentially incompatible; that is, tourism only generated value when it occurred within a reserve.…”
Section: Discussionsupporting
confidence: 92%
“…Another conclusion (which probably does not need to be explained) is that optimal reserves are prominent when intrinsic habitat value is high. This result is consistent with the findings of Viana et al (2017), who found the size of reserves should be larger with increasing tourism value, which was tied to increased stock density. In their analysis, however, tourism and fishing were essentially incompatible; that is, tourism only generated value when it occurred within a reserve.…”
Section: Discussionsupporting
confidence: 92%
“…There are a number of other possible indicators that could show a change due to the implementation of the reserve. Notably, one often cited in the literature is additional benefits, such as tourism [51]. However, it is unlikely that the evaluated communities will experience tourism benefits due to their remoteness and the lack of proper infrastructure to sustain tourism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fisheries, the other main market benefits of MPAs that have been most documented are those related to tourism (Alban et al, 2008(Alban et al, , 2011Rees et al, 2015;Viana et al, 2017;Haines et al, 2018;Davis et al, 2019), although numerous models are theoretical. In fact, marine reserves, and the effects they produce on the ecosystem, have shown a great capacity to reconcile fishing with other activities like tourism (Pérez-Ruzafa et al, 2008b).…”
Section: Mpas Produce Economic Benefits For Local Populationsmentioning
confidence: 99%